Cost projection of combined cycle power plants equipped with post-combustion carbon capture - Díaz-Herrera, Pablo R.; Romero-Martínez, Ascención; Ascanio, Gabriel (Frontiers in Energy Research, 2022)
This work aims to analyze the cost projection of natural gas combined cycles (NGCC) with post-combustion carbon capture (PCC) technology for two promising power plant configurations, namely: conventional NGCC and exhaust gas recirculation (EGR). A thermo-economic analysis was performed considering the second-law efficiency for the CO2 separation process (η_2nd) and the CO2 avoided cost (CAC) as main indicators. Several critical variables influencing the overall cost of the plant were considered, such as the work required for solvent regeneration (W_regen), technology maturity, learning rate, carbon tax credit, and carbon capture level (85%, 90%, and 95%). A hybrid method combining engineering-economic and experience-curve approaches was used to estimate the costs of Nth-of-a-kind (NOAK) plants. The results showed that NOAK plants could potentially decrease the levelized cost of electricity (LCOE) by 10%-11%, and the CAC by 21-23%, compared with first-of-a-kind (FOAK) plants. EGR at 85% capture level showed the best economic performance among the study cases evaluated, with a CAC equal to 102.5/tCO2. At an 85% capture level, the CAC for the conventional NOAK NGCC plant is 104.1/tCO2; maintaining this same CAC value, the carbon capture rate could increase from 85% to 90.8% if EGR configuration is implemented. Finally, from the findings of this research, it is concluded that the CAC for NOAK plants is expected to be, in the best scenario, as low as 69/tCO2. Therefore, these plants might need at least a similar carbon tax value to ensure their operation during their useful life.